Assessing the comparability of standardized patient and physician evaluations of clinical skills. - Boulet,JR; McKinley,DW; Norcini,JJ; Whelan,GP (Adv Health Sci Educ Theory Pract, 2002)
Accumulating evidence to defend decisions based on scores from evaluations is an ongoing process. The purpose of this investigation was to gather additional data to support the validity of inferences made from scores on the Educational Commission for Foreign Medical Graduates' Clinical Skills Assessment (CSA). This was accomplished by contrasting CSA candidate scores, and pass/fail decisions, with those obtained from the American Board of Internal Medicine's Mini-CEX (Clinical Evaluation Exercise). Data gathering performance based on the number of unweighted history taking and physical examination checklist items adequately predicted the global ratings provided by physician observers. CSA ratings of doctor-patient communication skills correlated with mini-CEX ratings of like constructs, indicating that physician observers, using mini-CEX rating scales, are able to make realistic assessments of interpersonal skills. These results provide evidence of the convergent validity of CSA scores.